2002
DOI: 10.1385/bter:86:3:193
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Determinations in Blood Cells

Abstract: As an essential nutrient involved in carbohydrate and lipid metabolism, chromium is of extraordinary importance for patients with diabetes. Plasma concentrations do not reflect the chromium supply; thus, we determined the element's content in blood cells in order to evaluate the body status. We investigated 86 blood donors (C) and 35 diabetics type 2 (Dm2). After the isolation of the blood cells by using a density centrifugation, the chromium concentrations were determined by electrothermal atomic absorption s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Some studies have reported a relation between T2DM and Cr levels in serum and blood cells [18, 19]. Rukgauer and Zeyfang [18] reported that T2DM patients have higher Cr content in the plasma, erythrocytes, and platelets and lower content in polymorphonuclear and mononuclear leukocytes compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported a relation between T2DM and Cr levels in serum and blood cells [18, 19]. Rukgauer and Zeyfang [18] reported that T2DM patients have higher Cr content in the plasma, erythrocytes, and platelets and lower content in polymorphonuclear and mononuclear leukocytes compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Rukgauer and Zeyfang [18] reported that T2DM patients have higher Cr content in the plasma, erythrocytes, and platelets and lower content in polymorphonuclear and mononuclear leukocytes compared with the control group. We found lower levels of serum Cr in patients with T2DM than in the control group.…”
Section: Discussionmentioning
confidence: 99%